"Smart" Catalysis with thermoresponsive ruthenium catalysts for miniemulsion ru‐mediated reversible deactivation radical polymerization cocatalyzed by smart iron cocatalysts. Issue 3 (23rd October 2018) - Bultz, Elijah; Ouchi, Makoto; Sawamoto, Mitsuo; Cunningham, Michael F.
ABSTRACT: This work reports the use of cocatalysts in addition to "smart" ruthenium catalysts for Ru‐mediated reversible deactivation radical polymerization (RDRP) in miniemulsion, allowing for the synthesis of final products with significantly reduced residual metal. Using amine cocatalysts in miniemulsion allows for high conversions (> 90%) in under 10 h. Two forms of ferrocene cocatalysts are also used, including "smart" thermoresponsive PEGylated ferrocene derivatives (FcPEG) and ferrocene containing surfactants (FcTMA). Using "smart" thermoresponsive cocatalyst at low concentrations, rate enhancements in BMA and BzMA polymerizations are observed, with good catalyst removability. Using the FcTMA cocatalyst surfactant, increasing monomer hydrophobicity is shown to increase the polymerization rate and initiator efficiency. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 305–312 Abstract : Two ferrocene cocatalysts are used in conjunction with "smart" thermosensitive ruthenium catalysts for Ru‐mediated reversible deactivation radical polymerization in miniemulsion, yielding final products with very low residual metal.